Enhancing environmental and social disclosure through board competencies: evidence from listed firms in Malaysia - Abdullah, Norhidayah; Raja Ahmad, Raja Adzrin; Azmi, Nurul Azlin; Samsuddin, Mas Ervina; Zakaria, Nor Balkish (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
The purpose of this study was to examine the effects of internal governance mechanisms on environmental and social (ES) disclosures. Firms with competent directors in the boardroom focussed on firm investments and achieve better disclosures. The population consisted of the top 100 publicly listed firms in Bursa Malaysia, with the final sample consisting of 180 firm-year observations from 2019 until 2022. Board competencies proxied by board size, board meeting, expertise, gender, independence, and internationalisation directorship were hand-collected from the annual reports, while financial data and ES scores were gathered from the Eikon Datastream. We found that board expertise, gender, and internalisation had a positive and significant relationship with ES disclosure. Furthermore, we also examined the effects of board competencies and ES disclosure separately and found that only board expertise and gender had a positive and significant relationship with environmental disclosure. However, board expertise, gender, independence, and internationalisation directorship had a positive and significant relationship with social disclosure. This study contributes to the extent of the literature by examining the board of directors’ effectiveness in promoting ES activities in the firms. In addition, this study offers practitioners insights into having a competent board to ensure better ES investments and transparency.